1999
DOI: 10.1093/humrep/14.12.3107
|View full text |Cite
|
Sign up to set email alerts
|

The SCID mouse: an experimental model for endometriosis

Abstract: The purpose of this study was to validate the suitability of the severe combined immunodeficient (SCID) mouse as an experimental model for endometriosis, by defining the morphological and histological features of induced endometrial implants, and characterizing specific biochemical properties of these implants. Human secretory endometrial tissues were injected into the peritoneal cavity of SCID/SCID CB17 mature female mice. Successful peritoneal implantation was observed in 55 of 57 (96.5%) SCID mice and consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
49
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(51 citation statements)
references
References 21 publications
1
49
1
Order By: Relevance
“…10 It was obvious in the H&E-stained sections that the xenografts are not necrotic or fibrotic, and vascularization was evident because of the presence of small vessels and red blood cells (Figure 2). Thus, our results confirmed that pretreatment with both Ad-COX-2 and Ad-VEGF-A provided a means of satisfactory tissue homeostasis with sustained proliferation and minimal apoptosis that were similar to the results of the matched control leiomyoma tissue.…”
Section: Commentmentioning
confidence: 98%
See 2 more Smart Citations
“…10 It was obvious in the H&E-stained sections that the xenografts are not necrotic or fibrotic, and vascularization was evident because of the presence of small vessels and red blood cells (Figure 2). Thus, our results confirmed that pretreatment with both Ad-COX-2 and Ad-VEGF-A provided a means of satisfactory tissue homeostasis with sustained proliferation and minimal apoptosis that were similar to the results of the matched control leiomyoma tissue.…”
Section: Commentmentioning
confidence: 98%
“…10 Humantissues serially passed in thesemice were shown to retain their morphologic and biochemical characteristics. 10 The aim of our study was to develop a reliable in vivo model of human uterine leiomyoma by using SCID mice implanted with human leiomyoma explants that were enhanced by transfection with an adenovirus carrying COX-2 and/or VEGF-A. …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Awwad et al, (1999) had successfully performed the implantation of endometriosis in mice (Mus musculus) with a success rate of 96.5%. We, therefore, investigated the effectiveness of curcumin in endometriosis treatment.…”
Section:  Corresponding Author: Auliafirmawatidrh@gmailcommentioning
confidence: 99%
“…Then, estrogen was injected intramuscularly in femoral biceps muscles on day 1 and 5 after the injection of female treatment endometrium. Thereafter, implantation of endometrial tissue was done on day-1 by injecting endometrial isolate intraperitoneally as much as 0.1 cc, equivalent to 0.6 grams of wet endometrial tissue (Awwad et al, 1999).…”
Section: The Making Of Endometriotic Mouse Modelsmentioning
confidence: 99%